Proceeding 2000 IEEE International Symposium on Visual Languages
DOI: 10.1109/vl.2000.874379
|View full text |Cite
|
Sign up to set email alerts
|

Tabular and textual methods for selecting objects from a group

Abstract: The accurate formulation of boolean expressions is a notorious problem in programming languages and database query tools. This paper studies the ways that untrained users naturally express and interpret queries, revealing some of the underlying reasons why this task is so difficult. Among the study ' IntroductionWe are applying human-computer interaction techniques to the design of new programming language features. Design decisions are resolved by looking to prior research for warnings about potential proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
(22 reference statements)
1
24
0
Order By: Relevance
“…Observations of novice programmers and database users have shown that users tend to confuse and with or, probably because these words are used ambiguously in natural language [GDCG90,PM00]. The more troublesome of the two operators seems to be and, since it can be used in natural language to mean not only Boolean conjunction ("I want candy bars that are chewy and sweet") but also disjunction ("I want candy bars from Hershey and Cadbury").…”
Section: Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of novice programmers and database users have shown that users tend to confuse and with or, probably because these words are used ambiguously in natural language [GDCG90,PM00]. The more troublesome of the two operators seems to be and, since it can be used in natural language to mean not only Boolean conjunction ("I want candy bars that are chewy and sweet") but also disjunction ("I want candy bars from Hershey and Cadbury").…”
Section: Goalsmentioning
confidence: 99%
“…In fact, programming style books often recommend redundant parentheses when the precedence or associativity is not completely obvious [KP99]. Unfortunately, parentheses are not an ideal solution either, because a number of studies have shown that novice users tend to misinterpret or ignore parentheses [GDCG90,PM00]. TC avoids precedence and associativity confusion by establishing a common rule for all operators, and avoids most parenthesis problems by structuring expressions with indentation.…”
Section: Goalsmentioning
confidence: 99%
“…However, there is strong empirical evidence that end users, who are by far the largest group of users of search engines, are not able to use Boolean operators correctly. For instance, Pane and Myers found that sometimes, when people say and, they actually mean or [11] (for example, "I am interested in blue and red cars" usually expresses the interest in cars that are red or blue.) This and/or confusion happens very frequently when keywords are used that are closely related in a concept hierarchy (for example, red and blue are both colors).…”
Section: Introductionmentioning
confidence: 99%
“…In our user study, match forms performed better than any of the purely textual representations we tested, including Boolean expressions [25]. Match forms helped the participants avoid some of the common problems they had with using the Boolean operators to construct textual expressions.…”
Section: Boolean Expressionsmentioning
confidence: 87%